PENGARUH PEMBERIAN TERAPI MADU TERHADAP TINGKAT NYERI PADA SAAT PEMASANGAN INFUS ANAK DENGAN HOSPITALISASI DI RSU X DENPASAR - Wishnuningsih, Aryanti; Juliawan, Dewa Gede; Suarriani, Ni Putu Dian (ARCHIVE OF COMMUNITY HEALTH, 2025)
ABSTRACT Hospitalization or inpatient treatment is a planned or emergency process that requires the child to stay in the hospital to undergo therapy and treatment until the child is sent home. This study aims to analyze the effect of giving honey therapy on the level of pain during infusion in children hospitalized at RSU X Denpasar. This research used a Post Test Control Design using a non-probability sampling technique involving 46 respondents who were divided into 2 groups, namely 23 control groups and 23 intervention groups. Respondents were given intervention in the form of honey therapy before the infusion was carried out. Then the researchers observed the child's pain level which was measured using the Wong Baker Pain Scale. The data was then tested using the Mann Whitney test and a significance value of 0.00 was obtained with a significance level of 0.05, which means there was an influence on the level of pain after giving honey therapy to children hospitalized at RSU X Denpasar (p<0.05). The results of the study showed that there was a decrease in the pain scale from moderate to mild, so this honey therapy can be recommended as a non-pharmacological therapy to reduce pain when installing a child's IV in health services. This intervention can be carried out in every health service but must be adapted to the existing circumstances and situations. Keywords:  honey therapy, child infusion, pain level